Spatio-Temporal Analysis of Ilorin Airport on the Land-Use of Ilorin Metropolis, Southwestern Nigeria - Ahmed, Nurudeen Onomhoale; Taiwo, Oyeniyi Solomon (Politeknik Negeri Batam, 2023)
This study investigates land-use patterns and changes in the vicinity of Ilorin Airport in Southwestern Nigeria using spatio-temporal analysis. Geographic information systems (GIS) and remote sensing techniques are employed to analyze land use dynamics from 1972 to 2018, and make a projection to 2078. Satellite images obtained from the United States Geological Survey and primary data collected through GPS serve as the main sources of information for the analysis. The findings reveal significant shifts in land use over the study period. A marked increase in built-up areas indicates urban expansion, while grassland areas experience a corresponding decrease. These changes are attributed to the development and growth of the airport and ongoing urbanization processes in the region. The results provide valuable insights into the impact of airport development and urbanization on land-use patterns in the study area. The study highlights the importance of employing GIS and remote sensing techniques in monitoring and analyzing land-use dynamics, enabling informed decision-making and planning processes. The research contributes to the existing knowledge on land-use changes associated with airport development and urbanization. It provides a foundation for further research in the field of land-use management and spatial planning. The outcomes of this study can inform policy and decision-makers, urban planners, and other stakeholders in developing strategies for sustainable land-use practices and mitigating the potential adverse effects of airport development and urban expansion.